2010
DOI: 10.1093/hmg/ddp590
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-function mutation in FGFR3 in mice leads to decreased bone mass by affecting both osteoblastogenesis and osteoclastogenesis

Abstract: Achondroplasia (ACH) is a short-limbed dwarfism resulting from gain-of-function mutations in fibroblast growth factor receptor 3 (FGFR3). Previous studies have shown that ACH patients have impaired chondrogenesis, but the effects of FGFR3 on bone formation and bone remodeling at adult stages of ACH have not been fully investigated. Using micro-computed tomography and histomorphometric analyses, we found that 2-month-old Fgfr3 G369C/1 mice (mouse model mimicking human ACH) showed decreased bone mass due to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 59 publications
6
105
0
Order By: Relevance
“…regulate osteogenesis by promoting or inhibiting osteogenic differentiation and mineralization of bone marrow stromal cells (BMSCs) (31,33). In this study, we further demonstrate that FGFR3, in addition to its direct regulation of osteogenesis, can also regulate bone formation and bone mass indirectly through its regulation of chondrogenesis.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…regulate osteogenesis by promoting or inhibiting osteogenic differentiation and mineralization of bone marrow stromal cells (BMSCs) (31,33). In this study, we further demonstrate that FGFR3, in addition to its direct regulation of osteogenesis, can also regulate bone formation and bone mass indirectly through its regulation of chondrogenesis.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, FGFR3 also regulates bone mass. Previous studies showed that adult Fgfr3 and Fgfr3IIIc knock-out mice displayed decreased bone mass (31,32), and ubiquitous gain-of-function mutations in FGFR3 also led to decreased bone mass in mice (33,35). FGFR3 can directly FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoclasts with FGFR1 deficiency (LysM-Cre mice) displayed decreased expression of genes related to osteoclast activity, including TRAP and MMP9, and exhibited abnormal bone remodeling with reduced osteoclast number and impaired osteoclast function ). On the other hand, osteoclast numbers and bone resorption area were increased in cultured bone marrow cells derived from Fgfr3 G369C/+ mice, suggesting that gain-of-function mutations in FGFR3 increase osteoclast activity, which contributes to decreased bone mass in these mice (Su et al 2010). …”
Section: Fgf Signaling In Osteoclastsmentioning
confidence: 99%
“…Indeed, chondrocyte-specific activation of Fgfr3 in mice was found to induce premature suture closure and indirectly enhance osteoblast differentiation through MAPK activation and BMP signaling (Matsushita et al 2009b). In long bones, gain-of-function FGFR3 mutations in chondrocytes, but not in osteoblasts, caused increased osteoclast recruitment, defective mineralization, and decreased trabecular bone mass, indicating that overactive FGFR3 signaling indirectly affects trabecular bone development (Su et al 2010;Mugniery et al 2012).…”
Section: Craniosynostosis Syndromesmentioning
confidence: 99%